Nanocrystalline Hydroxyapatite/Si Coating by Mechanical Alloying Technique - Ahmed E. Hannora; Alexander S. Mukasyan; Zulkhair A. Mansurov (Bioinorganic Chemistry and Applications)
A novel approach for depositing hydroxyapatite (HA) films on titanium substrates by using mechanical alloying (MA) technique has been developed. However, it was shown that one-hour heat treatment at 800°C of such mechanically coated HA layer leads to partial transformation of desired HA phase to beta-tri-calcium phosphate (β-TCP) phase. It appears that the grain boundary and interface defects formed during MA promote this transformation. It was discovered that doping HA by silicon results in hindering this phase transformation process. The Si-doped HA does not show phase transition to β-TCP or decomposition after heat treatment even at 900°C.